Diversitas Perifiton Pada Daun Lamun Enhalus acoroides Di Perairan Karangsewu, Teluk Gilimanuk, Taman Nasional Bali Barat - Arliza Cynthia Razali; Ni Luh Watiniasih; Ayu Putu Wiweka Krisna Dewi (Program Studi Manajemen Sumberdaya Perairan, Fakultas Kelautan dan Perikanan, Universitas Udayana, 2019)
Seagrass is one of the important ecosystems, both physically and biologically. In addition, seagrasses also act as the main producers in food webs, become shelters, forage and breed various types of biota, one of which is periphyton. Periphyton is a collection of micro-organisms and plants (a collection of cyanobacteria and microinvertebrate algae) that live around the epiphyton in the waters. This study aims to determine the type composition and diversity of periphyton that attaches to seagrass leaves. The method used is the observation method. Data retrieval is done by the transect line method. Periphyton compositions obtained were as many as 23 types of periphyton consisting of 4 classes, namely Bacillariophyceae (16 species), Cyanophyceae (4 species), Euglenophyceae (1 species) and Chlorophyceae (2 species). The highest composition was found in the Bacillariophyceae class, which was 63% and the lowest composition was in the Chlorophyceae class of 1%. Periphyton diversity includes diversity index, uniformity index and dominance index. Where the value of the diversity index is classified as moderate, perifiton uniformity index value is high, and the perifiton dominance index value is relatively low.